Investigation of stx1 stx2 eaeA and hlyA virulence genes in Escherichia coli isolates from healthy rabbits - SAMANTA, I; WANI, S A; BHAT, M A (The Indian Journal of Animal Sciences, 2011)
Isolates (148) of Escherichia coli (E. coli) were recovered from 200 faecal samples of apparently healthy rabbits. Eighty (54.05%) were typable and belonged to 25 different ’0’ serogroups (OS, 08, 020, 025, 027, 028, 032, 037’) 3 , 049,076,081,085, 088, 092, Ol?1, 0102,0110,0120,0123, 0131, 0146,0157, 0166 and 0168). ThirtySIX Isolates could not be typed and 52 were Identified as rough. All E. coli isolates were analysed by multiplex polymerase chain reaction (m-PeR) for the pre.sence ofstxl’ tx2’ eaeA and hlyA genes. Only 4 (2.7%) E. coli isolates belonging to 05,025 and 0131 serogroups carned only one VIrulence gene (eaeA) studied. None ofthe E. coli isolates possessed stx or hlyA genes. Â